COVID‐19 vaccination in pediatric solid organ transplant recipients—Current state and future directions. (2nd June 2021) - L'Huillier, Arnaud G.; Ardura, Monica I.; Chaudhuri, Abanti; Danziger‐Isakov, Lara; Dulek, Daniel; Green, Michael; Michaels, Marian G.; Posfay‐Barbe, Klara M.; Vàsquez, Luciola; Benden, Christian
Abstract: Background: Population‐level COVID‐19 immunization will play a key role in slowing down the SARS‐CoV‐2 pandemic on a global scale and protect the most at‐risk individuals. Thanks to a formidable universal effort, several SARS‐CoV‐2 vaccines have been marketed less than a year since the first documented COVID‐19 case, with promising safety, efficacy, and immunogenicity results in adults. As children were not included in the initial trials, no vaccine is currently approved for individuals <16 years of age. Similarly, immunosuppressed individuals, such as solid organ transplant recipients, were excluded from initial vaccine trials, limiting the understanding of vaccine immunogenicity and safety in this at‐risk population. Thus, data regarding COVID‐19 vaccination in pediatric solid organ transplantation recipients are currently lacking. Methods: Members of the International Pediatric Transplant Association review the current general status of COVID‐19 vaccines focusing on pediatric‐specific issues. Results: This review provides an overview of COVID‐19 vaccines in pediatric SOT recipients and highlights the current paucity of data in both pediatric and transplant settings in terms of safety, immunogenicity, and clinical efficacy. Conclusions: Vaccine trials including children and transplant recipients are underway and will be necessary to characterize COVID‐19 vaccine safety, immunogenicity, and efficacy, which will determine potential future research directions.